2013
DOI: 10.1007/s11096-013-9898-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmaceutical care on adherence, hospitalisations and mortality in elderly patients

Abstract: Pharmaceutical care given to our elderly polypharmacy patients made no significant impact on medication adherence, hospitalisation or mortality, when compared to comparable control patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 25 publications
1
54
1
14
Order By: Relevance
“…Many studies have set out to assess the effectiveness of PhC activities for years, and several have shown some positive impact of educational intervention (verbal or written information) on patients' health outcomes compared to non-intervention, mainly by improving compliance and adherence to drug therapy [11,12]. For European studies in particular, we conducted a specific literature search 1 and found seven studies on PhC in the community [13][14][15][16][17][18][19], all from northern countries ( Table 1). Only one study involved general practitioners (in addition to pharmacists) [14], and all but one [16] concluded in favor of PhC and were only co-authored by pharmacists.…”
Section: Phc Definition and Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have set out to assess the effectiveness of PhC activities for years, and several have shown some positive impact of educational intervention (verbal or written information) on patients' health outcomes compared to non-intervention, mainly by improving compliance and adherence to drug therapy [11,12]. For European studies in particular, we conducted a specific literature search 1 and found seven studies on PhC in the community [13][14][15][16][17][18][19], all from northern countries ( Table 1). Only one study involved general practitioners (in addition to pharmacists) [14], and all but one [16] concluded in favor of PhC and were only co-authored by pharmacists.…”
Section: Phc Definition and Activitiesmentioning
confidence: 99%
“…For European studies in particular, we conducted a specific literature search 1 and found seven studies on PhC in the community [13][14][15][16][17][18][19], all from northern countries ( Table 1). Only one study involved general practitioners (in addition to pharmacists) [14], and all but one [16] concluded in favor of PhC and were only co-authored by pharmacists.…”
Section: Phc Definition and Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, os idosos são propensos a alterações e deficiências nutricionais por distintos fatores como desnutrição e desidratação, hipo-albuminemia e, consequente aumento da fração livre do fármaco, aumento da gordura corporal e redução do tecido muscular, deficiência nutricional de proteínas e micronutrientes, que podem alterar o metabolismo do fármaco; e alterações da função renal, ocasionando risco de toxicidade. As alterações supracitadas podem modificar os efeitos de agentes sedativos, cardiovasculares, diuréticos e outras classes terapêuticas muito utilizadas por idosos (19,20 (21).…”
Section: Por Meio Dessas Possibilidades De Interaçõesunclassified
“…13 Despite ample evidence to support the roles of pharmacists in providing medication management services, studies for home-based medication reviews (HBMR) have shown conflicting results. 5,13,14 In the "Home based medication review" (HOMER) randomized controlled trial (2005), HBMR was counterintuitively associated with a higher rate of hospital admissions, and did not significantly improve quality of life or reduce mortality among elderly patients. 5 The POLYMED study showed cost savings, mainly as a result of reduced prescribing, but no significant improvements were seen in clinical outcomes and quality of life among elderly patients.…”
Section: Introductionmentioning
confidence: 99%